Movimento de interface para duas equações de reação-difusão - Biesdorf, João (2007)
In this work, following [15], we will use the technique of matched asymptotic expansions to study the movement of interface for the solutions of an advection-reaction- difuusion equations and the equation of reaction-difusion with spatially of inhomogeneous reaction term. We will get that the equations of such movements are equal. Also we will study a system of equations without the drift term and will compare the movement of its interfaces with the equation of the model of chemotaxis considered by Mimura and TsujiKawa [13] and [14]. Keywords: Asymptotic expansions, mean curvature motion.